EFEKTIVITAS PEMBELAJARAN DARING PENDIDIKAN JASMANI KESEHATAN DAN REKREASI DENGAN PEMANFAATAN APLIKASI PENJASPEDIA PADA MASA PANDEMI COVID-19 DI SEKOLAH DASAR SE-KECAMATAN JONGGOL - Faisal Adlun; Hasan Basri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
COVID-19 is a new type of virus that was discovered in Indonesia in March 2020. The confirmed patient data as of March 1, 2021, were 1,341,314 people from all over Indonesia. The Covid-19 outbreak has brought changes in the movement of the economic structure and mobility of the people evenly. One of them is that the learning system which was initially implemented offline and later became online has a significant negative impact on productivity that can be felt by parents and students themselves. One of the lessons that must be online is sports, where sports activities require movement in their implementation. This research uses a survey method and uses primary data, namely data sources that are directly obtained and collected in the field. This research is a qualitative research with library methods and uses a data collection technique in the form of a questionnaire. Based on the results of research on the readiness of PJOK teachers in carrying out online learning, it shows that most of them stated their readiness to carry out online learning, related to the online learning system that there was a significant increase in the online learning system, and related to online learning media showed that there was a significant increase in the use of media online learning.